(untitled) - Kovac, Bronislav; Matejka, Rostislav (Doprava a spoje, 2006)
There are two paralel legislative systems for light lorry's (category N1) engine exhaust emissions in Europe. Since 1993 the systems are harmonized. It means, that measured parameters, test mode, used equipment and specified limities are the same. The emision limit Euro 4 is going to take effect since 10/2006 and the limit Euro 5 since 6/2009. The paper describes technical posssibilities how to achieve these limits through catalytic reduction using water solution of carbamide AdBlue + DENOXTRONIC made by BOSCH and recirculation of exhaust fumes.